2009
DOI: 10.1016/j.pain.2009.02.021
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of a tailored barriers intervention for Cancer Information Service (CIS) callers in pain

Abstract: Cancer pain management can be improved by overcoming patients' attitudinal barriers to reporting pain and using analgesics. A simple cost-effective barriers intervention designed to reach a large number of persons with cancer has not yet been tested. Such an intervention should be tested against barriers' assessment-alone, as well as no-treatment control. The purpose of this study was to test the efficacy and the cost-effectiveness of a Tailored Barriers Intervention (TBI), an educational intervention tailored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
0
26
1
Order By: Relevance
“…Differences in patient pain outcomes between the groups did not reach statistical significance. Patients in the intervention group were more likely to have a reduction in usual pain levels than control Ward [65] RID pain intervention targeting individual patients or dyad of patient plus carer/significant other Usual care x x No improvement in pain outcomes in intervention group compared to control, and including carers did not affect outcomes Wells [66] 15 min video for patients and carers, <30 min individualized pain and analgesic assessment, access to a pain hot line, weekly follow up telephone calls from nurse specialist who did not change analgesics but could suggest patient contact oncologist…”
Section: Results Of Systematic Reviewsmentioning
confidence: 96%
“…Differences in patient pain outcomes between the groups did not reach statistical significance. Patients in the intervention group were more likely to have a reduction in usual pain levels than control Ward [65] RID pain intervention targeting individual patients or dyad of patient plus carer/significant other Usual care x x No improvement in pain outcomes in intervention group compared to control, and including carers did not affect outcomes Wells [66] 15 min video for patients and carers, <30 min individualized pain and analgesic assessment, access to a pain hot line, weekly follow up telephone calls from nurse specialist who did not change analgesics but could suggest patient contact oncologist…”
Section: Results Of Systematic Reviewsmentioning
confidence: 96%
“…Several studies using the patient education approach to pain management showed reduced patient-related barriers and improved pain symptoms; [12][13][14][15] however, a tailored barriers intervention resulted in significantly lowered attitudinal barriers scores but did not improve pain outcomes. 16 Cancer pain is a complicated symptom that is frequently reported with other symptoms such as fatigue, depression, and anxiety. Coexisting depression might be one obstacle to pain management in cancer patients.…”
mentioning
confidence: 99%
“…40,41 Model programs have emphasized patient teaching interventions including the use of pain assessment tools, strategies to dispel misconceptions, and patient coaching regarding the reporting and documenting of their symptoms. 42,43 The ''Passport to Comfort'' intervention was designed and implemented in response to the overwhelming evidence of the impact of these barriers on symptom management, and the intent to move beyond descriptive studies to test innovative models that would eliminate these barriers in palliative care settings.…”
mentioning
confidence: 99%